On computational interdisciplinary modeling for reliability assessment of high‐speed train – bridge interaction. Issue 1 (17th December 2018) - Adam, Christoph; Hirzinger, Benjamin; Oberguggenberger, Michael; Salcher, Patrick
Abstract: Bridge and crossing high‐speed train represent an uncertain interacting dynamic system of high complexity with, in general, time‐dependent system matrices. Thus, full reliability assessment of this system can only be conducted efficiently in an interdisciplinary approach, bringing together the disciplines of structural mechanics, engineering mathematics, and high performance computing. This contribution gives a brief summary on computational modeling issues of uncertain bridge‐train interaction, its efficient stochastic simulation, and an outline of pros and cons of different strategies is provided.